Answer:
C
Step-by-step explanation:
3x^2 * -x =-3x^3
3x^2 * 2. =6x^2
4x* -x =-4x^2
4x * 2 = 8x
-5 * -x = 5x
-5 * 2 = -10
6x^2 + -4x^2 = 2x^2
8x+5x = 13 x
Ans: -3x^3 + 2x^2 + 13x -10
Marla Paid 72$ or 71.99$ because 20% is 18$ so you subtract 90 by 18.
Change 4 feet to inches
4 feet is 48 inches
48-10=38
Answer:
Range of Function : { - 9, - 5, - 1, 4 }
Step-by-step explanation:
We know that y = 2x - 5 provided the domain ( x - values ) { - 2, 0, 2, 4 }. Let us substitute each element in this set of domain as x in the equation "y = 2x - 5" as to solve for the y - values, otherwise known as the range of the function.
{ - 2, 0, 2, 4 }
y = 2( - 2 ) - 5 = - 9,
y = 2( 0 ) - 5 = - 5,
y = 2( 2 ) - 5 = - 1,
y = 2( 4 ) - 5 = 4
We have the set of y - values as { - 9, - 5, - 1, 4 }. This is the range of our function.